Accuracy of PCR targeting different markers for Staphylococcus aureus identification: a comparative study using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry as the gold standard. (March 2018) - Saraiva, Mauro M.; De Leon, Candice M.; Santos, Silvana C.; Stipp, Danilo T.; Souza, Miliane M.; Santos Filho, Lauro; Gebreyes, Wondwossen A.; Oliveira, Celso J.
Staphylococcus aureus is considered a major pathogen in veterinary and human medicine, and the emergence of multidrug-resistant strains, such as livestock-associated methicillin-resistant S. aureus, means that reliable, inexpensive, and fast methods are required to identify S. aureus obtained from animal sources. We tested the accuracy of a PCR targeting the genes fem A, nuc, and coa in identifying S. aureus from animals. A total of 157 Staphylococcus spp. isolates were examined by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry; 18 different Staphylococcus species were identified. Of 68 S. aureus isolates, the genes fem A, nuc, and coa were found in 61, 53, and 32 isolates, respectively. Considering MALDI-TOF as the gold standard, the PCR assays targeting all 3 genes showed 100% specificity; the sensitivity values were 89.7, 77.9, and 47.0% for fem A, nuc, and coa, respectively. Sensitivity was 100% when fem A and nuc markers were targeted simultaneously. These results confirm PCR as an accurate method to identify S. aureus species from animal sources and strongly suggest the simultaneous use of primers targeting fem A and nuc genes.